(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2017)
At the end of November 2016, a unique and intruding art project took place in the city of Hamburg, Germany, a result of collaboration between German artists and a Chinese artist, who all seek to commemorate the Chinese victims who lived in the city pre- World War II but had to suffer the injustices of the Nazi regime. The project lasted three days and was presented in various locations throughout the city, while including many artistic mediums alongside scholarly work. By referring to the main events of that weekend, the paper traces after a “forgotten” past that many people refuse to look at, not to say to take responsibility for it, while in contrast, the art continues to extract it from the depths of oblivion and forced amnesia – to the dismay of many.